Tinjauan Yuridis Klausul Take or Pay dan Gas Make Up dalam Kontrak Jual Beli Gas di Indonesia serta Akibat Hukumnya - Krisologus, Petrus; Sinaga, Niru Anita; Sudarto, Sudarto (LITERATUS, 2025)
Sale and purchase is a business activity aimed at seeking profit. In a sales transaction, there is a party selling goods and another party buying them according to the agreement. The take-or-pay contract is a sales agreement with a condition where the buyer is obliged to take a minimum quantity within a certain period, or even if the buyer does not take or takes less than the required minimum quantity, the buyer still has to pay the seller the price of the minimum quantity. Gas make-up is the buyer's right to take a certain volume of gas that has been paid for as a result of the take-or-pay arrangement. In practice, there are still disputes in the application of this clause due to the presence of significant factors beyond the control of the parties in its fulfilment. Therefore, further research will be conducted on the regulation of the take-or-pay clause and gas make-up in gas sales contracts in Indonesia and the legal consequences of the application of the take-or-pay clause and gas make-up in gas sales contracts in Indonesia. The research method used in this study is the normative juridical research method. The research findings reveal the regulation of the take-or-pay clause and gas make-up in gas sales contracts in Indonesia, including special/specific sales agreements. Sales agreements with the take-or-pay contract clause and gas make-up can be applied/implemented as long as there is an agreement by the parties because they do not conflict with the positive law in force in Indonesia, do not violate public order and decency, and are even in line with Article 1493 of the Civil Code. The legal consequence of the application of the take-or-pay clause and gas make-up in gas sales contracts in Indonesia is that the buyer still has to pay for the goods that were not taken, and the seller must provide the gas make-up during the contract period. Based on the research results, for improvement, new regulations related to the take-or-pay clause and gas make-up in gas sales contracts are to be made in the Law, legislation, government regulations, and the Minister of Energy and Mineral Resources Regulation in accordance with the applicable rules and the legislators, government regulations, and the Minister of Energy and Mineral Resources Regulation to provide certainty on the take-or-pay clause and gas make-up in gas sales contracts, especially when the gas has not passed the upstream delivery point.